Comparison of Vacuum MALDI and AP-MALDI Platforms for the Mass Spectrometry Imaging of Metabolites Involved in Salt Stress in Medicago truncatula - Keller, Caitlin; Maeda, Junko; Jayaraman, Dhileepkumar; Chakraborty, Sanhita; Sussman, Michael R.; Harris, Jeanne M.; Ané, Jean-Michel; Li, Lingjun (Frontiers in Plant Science, 2018)
Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) is routinely used to determine the spatial distributions of various biomolecules in tissues. Recently, there has been an increased interest in creating higher resolution images using sources with more focused beams. One such source, an atmospheric pressure (AP) MALDI source from MassTech, has a laser capable of reaching spatial resolutions of 10 μm. Here, the AP-MALDI source coupled with a Q Exactive HF Orbitrap platform is compared to the commercial MALDI-Orbitrap LTQ XL system using Medicago truncatula root nodules. AP-MALDI parameters, such as the S lens value, capillary temperature, and spray voltage, were optimized on the Q Exactive-HF platform for optimal detection of plant metabolites. The performance of the two systems was evaluated for sensitivity, spatial resolution, and overall ability to detect plant metabolites. The commercial MALDI-Orbitrap LTQ XL was superior regarding the number of compounds detected, as at least two times more m/z were detected compared to the AP-MALDI system. However, although the AP-MALDI source requires a spatial resolution higher than 10 μm to get the best signal, the spatial resolution at 30 μm is still superior compared to the 75 μm spatial resolution achieved on the MALDI platform. The AP-MALDI system was also used to investigate the metabolites present in Medicago truncatula roots and root nodules under high salt and low salt conditions. A discriminative analysis with SCiLS software revealed m/z ions specific to the control and salt conditions. This analysis revealed 44 m/z ions present at relatively higher abundances in the control samples, and 77 m/z enriched in the salt samples. Liquid chromatography-tandem MS was performed to determine the putative molecular identities of some of the mass ions enriched in each sample, including, asparagine, adenosine, and nicotinamine in the control samples, and arginine and soyasaponin I in the salt treated samples.